Formulation of Rabbit Feed Pellet from Palm Kernel Cake (PKC) - Nurul Ismalina, Ismail; Nor Surayah, Osman; Izume Ayuna, Mohammed Kamil; Nurul Nabihah, Rahman; Muhammad Farhan, Hanafi; Mohd Ariff, Rustam; Norzahir, Sapawe (Elsevier, 2019)
Product of palm oil industries in Malaysia such as palm kernel cake (PKC) has potential to be formulated as animal feed. The focus of this study is to utilized PKC by converting it to feed pellet that suitable for animal consumption. To ensure that the PKC can be used as animal feed, the present of protein content was investigate using Fourier-transform infrared spectroscopy (FTIR). The percentage of protein, fat and carbohydrate in PKC as well as other ingredients analysed by means of proximate analysis. The crude protein (CP) is 17.18%, fat of 4.18% while carbohydrate is 63.03%, which are the major concern for rabbit feeding. Pelletizing process takes place after formulation been made by using the Pearson Square method with known protein requirement. Produced pellet chemical composition and physical properties as well as the toxic level was analysed prior to feeding. The analysed pellet contained 14.6% of protein, 13.2% of fibre, 10.3% of fat and 9.85 of moisture content that is adequate for rabbit nutrient requirement. Feeding test display increase in weight of tested rabbit after three weeks of PKC pellet consumption and no mortality.